1986
DOI: 10.1111/j.1432-1033.1986.tb09503.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of ligands to horse liver alcohol dehydrogenase lacking zinc ions at the active sites

Abstract: 1. The zinc‐deficient enzyme binds the fluorescence probes for the enzyme substrate pocket (auramine O, 13‐ethylberberine, chlorprothixene and acridine orange) more tightly than the native enzyme, whereas 1‐anilinonaphthalene 8‐sulphonic acid is bound with comparable affinity. 2. The use of fluorescence probes as reporter ligands revealed that the formation of binary complexes between the zinc‐deficient enzyme and aldehydes is possible (as with the native enzyme) and confirmed an increased affinity of coenzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Apart from playing a structural role, Zn 2+ can also play a regulatory role in electron transfer, substrate oxidation−reduction, and transport processes. Furthermore, Zn 2+ can play a catalytic role in (i) facilitating the ionization of a first-shell water molecule to a nucleophilic hydroxide ion in proteins such as carbonic anhydrase , and metallo-β-lactamase or (ii) stabilizing the negatively charged intermediate of enzymes such as carboxypeptidase A , and alcohol dehydrogenase. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from playing a structural role, Zn 2+ can also play a regulatory role in electron transfer, substrate oxidation−reduction, and transport processes. Furthermore, Zn 2+ can play a catalytic role in (i) facilitating the ionization of a first-shell water molecule to a nucleophilic hydroxide ion in proteins such as carbonic anhydrase , and metallo-β-lactamase or (ii) stabilizing the negatively charged intermediate of enzymes such as carboxypeptidase A , and alcohol dehydrogenase. , …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Zn 2+ can play a catalytic role in (i) facilitating the ionization of a first-shell water molecule to a nucleophilic hydroxide ion in proteins 20 such as carbonic anhydrase 21,22 and metallo-β-lactamase 23 or (ii) stabilizing the negatively charged intermediate of enzymes such as carboxypeptidase A 24,25 and alcohol dehydrogenase. 26,27 Interestingly, a survey of Zn-proteins in the Protein Data Bank 28,29 (PDB) has shown that catalytic and structural zinc † Academia Sinica. ‡ National Tsing Hua University.…”
Section: Introductionmentioning
confidence: 99%